Sustainable manufacturing. Bibliometrics and content analysis - Yogesh Bhatt; Karminder Ghuman; Amandeep Dhir (Elsevier Ltd, 2022)
Businesses have practiced and examined lean and green manufacturing principles for the last 25 years, but the sustainability challenges that we face today are still significantly potent. This context creates a need to critically examine the research and practice in this domain to determine the gaps and propose solutions. To achieve that, we applied a two-tier analysis constituting bibliometric and content analyses for developing the intellectual structure of sustainable manufacturing (SM) literature. The study also produced a comprehensive framework to provide a granular understanding of SM literature. The framework demonstrates different paradigms of SM literature as well as the conceptual and methodological advancement of the research frontiers in the domain. The outcomes of the research comprise implications for researchers, managers, and policymakers. The study concludes that most empirical work focuses on the relationship of lean and green practices with organizational and environmental performance, but the role and criticality of sustainability are significantly underrepresented in SM literature. Based on our findings, we call for the integration of sustainability principles, that is, sustainable development goals (SDGs), circular economy, life cycle engineering, and corporate sustainability assessment with SM research.